Water and sociality in Khayelitsha: an ethnographic study - Kongo, Minga Mbweck (Social Anthropology, 2023)
This study examines forms of social relationships created around unequal municipal water distribution in South Africa. Using the case of Khayelitsha, the study investigates residents' use of water to sustain their livelihood and build personhood. Water mobilises the formation of relationships in myriad ways. How residents, collectively and individually, imagine, negotiate and construct their future pathways around resources available to them in a social group is explored. Ethnographic tools are used to address how social formations are created around municipal water in Khayelitsha. The study looks into how inequalities related to access to water in Cape Town are produced with inequitable development patterns. Using incompleteness and conviviality as framework, the study seeks to understand how ideas of social formation, belonging, marginality, and physical and social mobility are produced, reproduced and contested around water. By focusing on the strategies deployed by residents, this study also seeks to describe the challenges of inadequate water access experienced by residents in less- provisioned areas. The multiple relations with, and complexities of, municipal water are chronicled, as well as how Khayelitsha residents think about, relate and respond to water. The empirical data reveal several structural issues characterising the formation of social relations: incompleteness, impoverishment, marginalisation, water access and minimal opportunities. Despite many challenges, frustration, and heavy reliance on communal taps, tanks, water trucks, and hydrants, shack dwellers particularly cherish an ideal of self-sufficiency with the limited amount of water they access. In this quest, they maintain social relations and resistance to the political economy of water. They achieve this by mobility from one settlement to another, maintaining a strong sense of community, belonging, social relationships, and household interdependence, connected to a sense of incompleteness and, to a more considerable extent, Ubuntu. This social practice is manifested in various forms: neighbourliness, water usage at communal points, land occupations, and strikes, amongst others. By combining the structural issues and aspects of social practices provided above, water is seen as a substance that constructs social formations through the phenomena of incompleteness and conviviality. The data were collected during several field visits between February 2020 and March 2021 through observation of interactions and participation in residents' social activities and formal and informal interviews and group discussions with a representative sample of residents in Khayelitsha.